2023
DOI: 10.1371/journal.pone.0276576
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of magnetohydrodynamics effects on a generalised power law fluid model of blood flow through a bifurcated artery with an overlapping shaped stenosis

Abstract: This paper presents a numerical analysis of blood flow in a diseased vessel within the presence of an external magnetic field. The blood flow was considered to be incompressible and fully developed, in that the non-Newtonian nature of the fluid was characterised as a generalised power law model for shear-thinning, Newtonian, and shear-thickening fluids. The impact of a transverse directed external magnetic field on blood flow through a stenosed bifurcated artery was investigated. The arterial geometry was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…The researchers noted an augmentation in heat transfer rate corresponding to the Grashof number, concomitant with reduced stenosis severity. Zain and Ismail (2023) analysed MHD effects on blood flow via a Gyrotactic microorganisms in bifurcated artery bifurcated artery with overlapping-shaped stenosis. The authors suggested that enhancing the magnetic number reduced the WSS at the constricted section of the stenosis throat.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers noted an augmentation in heat transfer rate corresponding to the Grashof number, concomitant with reduced stenosis severity. Zain and Ismail (2023) analysed MHD effects on blood flow via a Gyrotactic microorganisms in bifurcated artery bifurcated artery with overlapping-shaped stenosis. The authors suggested that enhancing the magnetic number reduced the WSS at the constricted section of the stenosis throat.…”
Section: Introductionmentioning
confidence: 99%
“…A computational study with Oldroyd-B nanofluid flow and magnetized gold-blood particles passing through the blood was conducted by (Tang et al, 2023a). Furthermore, literature regarding magnetized gold-blood nanofluid stenosis narrow arteries, blood flow via arteries with overlapping shaped stenosis, and vertical porous multiple stenoses can be traced by (Zain and Ismail, 2023a;Tang et al, 2023b;El Kot and Abd Elmaboud, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that an inclined magnetic field could have important implications for the diagnosis and treatment of various cardiovascular disorders. Zain et al (Zain and Ismail, 2023b) explored the numerical results regarding the effects of MHD on blood flow by taking the mathematical model of power and the law fluid model. The latest study related to the influence of MHD, Dufour, and Soret effects on blood through a stenosed artery and keeping variable viscosity is established by Mishra et al (Mishra et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…These include an unhealthy diet, insufficient physical activity, tobacco use, elevated blood pressure and cholesterol levels, obesity, diabetes, and a family history of CVDs, among others. Cardiovascular diseases (CVDs) have the potential to inflict harm upon various components of the cardiovascular system, such as the heart, blood vessels, and other organs [16][17][18][19][20]. This can occur as a result of conditions such as coronary artery disease, heart failure, peripheral artery disease, aortic aneurysms, and arrhythmias [21].…”
Section: Introductionmentioning
confidence: 99%